2000
DOI: 10.1046/j.1365-2028.2000.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in woody vegetation cover in the Kruger National Park, South Africa, between 1940 and 1998

Abstract: Changes in the cover and density of shrubs and trees were assessed from aerial photographs (1940, 1974 and 1998) as well as from fixed‐point photographs taken in 1984 and 1996 in the Kruger National Park, South Africa. Woody cover (trees and shrubs combined) increased by 12% on granite substrates but decreased by 64% on basalt substrates over the past 58 years. Both these figures are expressed in terms of the initial values, respectively. The density of the large tree component of woody vegetation decreased on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
171
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(175 citation statements)
references
References 21 publications
(11 reference statements)
4
171
0
Order By: Relevance
“…Indeed, the decrease of the large-tree vegetation component in the Kruger National Park (South Africa) has been attributed to increased elephant densities as a consequence of the large number of AWPs here. Sequential photography revealed that the density of trees >5 m decreased in the Kruger Park by up to 38% on basalt-derived soils within a 12-year study period (Eckhardt et al 2000). While the authors of this study were cautious to attribute the observed tree density decrease to the growing elephant population alone, they suggested the closing of AWPs as a possible management measure to be taken, should large-tree density further decrease.…”
Section: Introductionmentioning
confidence: 91%
“…Indeed, the decrease of the large-tree vegetation component in the Kruger National Park (South Africa) has been attributed to increased elephant densities as a consequence of the large number of AWPs here. Sequential photography revealed that the density of trees >5 m decreased in the Kruger Park by up to 38% on basalt-derived soils within a 12-year study period (Eckhardt et al 2000). While the authors of this study were cautious to attribute the observed tree density decrease to the growing elephant population alone, they suggested the closing of AWPs as a possible management measure to be taken, should large-tree density further decrease.…”
Section: Introductionmentioning
confidence: 91%
“…Low recruitment rates of large tree species have also been reported by Holdo (2003) and Caro et al (2005). In addition, open savannahs become denser due to bush encroachment which is often the result of landscapes being over-grazed (Jeltsch et al 1997;Tobler et al 2003) and because of poor fire management (Eckhardt et al 2000). Since bush-encroached areas are mostly dominated by small and densely growing trees, tree size might be important in influencing grass quality and structure.…”
Section: Introductionmentioning
confidence: 94%
“…2 Relationship between the elephant density (N/km 2 ) and the overall tree stem density (N/km 2 ) (a), the number of stems per tree (b) and the estimated total consumption of browse (filled squares) and grass (open squares) of the relevant herbivores depicted as a percentage of the total consumption excluding elephants in Sabi Sand WildtuinMalaMala complex (c) (Fritz et al 2002;Kohi et al 2011;Valeix et al 2011;Kohi 2013). The impact of elephant may be site-or contextdependent (Guldemond and Van Aarde 2008) and varies spatially within KNP (Eckhardt et al 2000). Elephant numbers in the Sabi Sand Wildtuin-MalaMala complex were strongly negatively correlated with densities of both small and large trees.…”
Section: Discussionmentioning
confidence: 90%
“…In the proximity of large perennial rivers, current elephant densities in the KNP exceed 1.5 animals/km 2 (Smit and Ferreira 2010). Elephant impacts can also vary spatially and can be site-or context-dependent (Eckhardt et al 2000;Guldemond and Van Aarde 2008). Communicated by M. Scandura This impact of elephants on trees in the system has raised the concern of scientists and managers alike (Whyte et al 1998;Van Aarde et al 1999;Van Aarde et al 2006;Kerley et al 2008), as the decline in woody cover could negatively affect the browsing species in the system.…”
Section: Introductionmentioning
confidence: 99%